Changes in delta‐9‐tetrahydrocannabinol (THC) and cannabidiol (CBD) concentrations in cannabis over time: systematic review and meta‐analysis. (7th November 2020) - Freeman, Tom P.; Craft, Sam; Wilson, Jack; Stylianou, Stephan; ElSohly, Mahmoud; Di Forti, Marta; Lynskey, Michael T.
Abstract: Background and aims: Cannabis products with high delta‐9‐tetrahydrocannabinol (THC) concentrations carry an increased risk of addiction and mental health disorders, while it has been suggested that cannabidiol (CBD) may moderate the effects of THC. This study aimed to systematically review and meta‐analyse changes in THC and CBD concentrations in cannabis over time (PROSPERO registration: CRD42019130055). Design: Embase, MEDLINE® and Epub Ahead of Print, In‐Process and Other Non‐Indexed Citations and Daily, Global Health, PsycINFO and Scopus were searched from inception to 27/03/2019 for observational studies reporting changes in mean THC and/or CBD concentration in cannabis over at least three annual time points. Searches and extraction were conducted by two independent reviewers. Random effects meta‐regression models estimated annual changes in THC and CBD for each product within each study; these estimates were pooled across studies in random effects models. Results: We identified 12 eligible studies from the USA, UK, Netherlands, France, Denmark, Italy and New Zealand. For all herbal cannabis, THC concentrations increased by 0.29% each year (95% CI: 0.11, 0.47), P < 0.001 based on 66 747 cannabis samples from eight studies, 1970–2017. For cannabis resin, THC concentrations increased by 0.57% each year (95% CI: 0.10, 1.03), P = 0.017 based on 17 371 samples from eight studies, 1975–2017. There was no evidence for changes in CBD in herbal cannabis [−0.01% (95% CI: −0.02, 0.01), P = 0.280; 49 434 samples from five studies, 1995–2017] or cannabis resin [0.03% (95% CI: −0.11, 0.18), P = 0.651; 11 382 samples from six studies, 1992–2017]. Risk of bias was low apart from non‐random sampling in most studies. There was evidence of moderate to substantial heterogeneity. Conclusions: Concentrations of delta‐9‐tetrahydrocannabinol (THC) in international cannabis markets increased from 1970 to 2017 while cannabidiol (CBD) remained stable. Increases in THC were greater in cannabis resin than herbal cannabis. Rising THC in herbal cannabis was attributable to an increased market share of high‐THC sinsemilla relative to low‐THC traditional herbal cannabis.